PSXII-14 Nutritional restriction induced oxidative stress might compromise mammary protein synthesis through inhibition of v-ATPase/mTORC1 signaling. (7th December 2018) - Zhong, H; Song, Y; Fang, Z; Feng, B; Zhang, X; Che, L; Lin, Y; Xu, S; Li, J; Wu, D; Fang, Z
Abstract: The objective of this study was to test whether and how nutritional restriction affected mammary gland metabolism during lactation. Lactating sows with restricted feed allowance (RFA), up to 76% of the control (CON) group, were used as the nutritional restriction model from postpartum day 0 to 28. Microdialysis and mammary venous cannulas methods were used to monitor postprandial dynamic changes of metabolites in mammary glands. At postpartum day 28, the RFA group showed higher (P < 0.05) loss of body weight and backfat than the CON group. And compared with the CON group, the adipose tissue of the RFA group had higher (P < 0.05) extracellular glutamate and insulin levels, increased (P < 0.05) mRNA abundance of hormone-sensitive lipase and adipose triglyceride lipase, and decreased (P < 0.05) mRNA abundance of vesicle associated membrane protein 8, pyruvate kinase, and lactate dehydrogenase. Moreover, compared with the CON group, the RFA group had increased (P < 0.05) malondialdehyde level, and decreased (P < 0.05) glutathione peroxidase (GPx) activity in ear vein plasma. Meanwhile, the RFA group had lower (P < 0.05) GPx activity and reduced (P < 0.05) taurine concentrations in mammary vein plasma than the CON group. It would appear that nutritional restriction increased lipolysis and insulin resistance of adipose tissues, enhanced body catabolism, and reduced the systemic and mammary antioxidant capacity. As for mammary glands, the RFA group had lower (P < 0.05) lysosomal v-ATPase activity, decreased (P < 0.05) protein expression of p-mTOR, p-S6K, p-4E-BP1 and β-casein than the CON group at postpartum day 28, suggesting attenuated mammary v-ATPase/mTORC1 signaling and reduced β-casein synthesis. Collectively, nutritional restriction induced systemic and mammary oxidative stress might damage mammary protein synthesis through inhibition of v-ATPase/mTORC1 signaling.